Modelling the Acoustic Properties of Baffles Made of Porous and Fibrous Materials - KOSAŁA, Krzysztof (Archives of Acoustics, 2024)
The research described in the article addresses the problem of measurement, prediction and practical use of the acoustic properties of materials determined in an impedance tube. The aim of the research was to develop a simple calculation model for the insertion loss of small machinery enclosures, based on the normal incidence sound transmission loss and the normal incidence sound absorption coefficient of porous and fibrous materials. Both experimental and model tests were carried out on materials such as mineral wool, melamine foam and rebonded polyurethane foam. Assessing the absorption properties of the tested porous and fibrous materials was performed using selected theoretical models, relating the calculations of the normal incidence sound absorption coefficient to measurements of this parameter conducted using an impedance tube. The application of the modified Allard and Champoux model brought the best results with the smallest discrepancies of the obtained results in relation to the experimental tests. Assessing the sound-insulating properties of the tested mineral wool was carried out using the proposed calculation model for the normal incidence sound transmission loss, relating the obtained results to measurements conducted using an impedance tube. The assessment of the sound-insulating properties of porous and fibrous materials was performed using the proposed calculation model for insertion loss, which was validated using two prototype test stands for determining the insertion loss of cubic enclosures, in this case with walls made of porous and fibrous materials. Satisfactory results were obtained for engineering applications in the calculation results using the proposed models with respect to measurements. The results may have practical applications in assessing the effectiveness of acoustic enclosures, in which the basic construction material is an appropriate porous or fibrous plate, selected to have both sound-absorbing and sound-insulating properties.